Introduction to the Models and Trends of Nepalese foreign policy modeling: Examining Nepalese Foreign Policy from Prithivi Narayan Shah to Present (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Prithivi Narayan Shah, a strong, visionary, and nationalist monarch, formed the cornerstone ofNepalese foreign policy after the creation of a single and United Kingdom. His foreign policy based onnon-alignment and neutrality is still important in light of geo-reality. Foreign policy images were notmaintained by successive regimes, though. It was difficult to make foreign policy decisions because ofthe habit of shifting foreign policy tacks with each new administration and leader. Country's existencehas always been threatened by its strategic position and the country's ongoing political turmoil. As aresult of the close proximity of two Asian countries and their security concerns, our independencebecame even more vulnerable. All of these factors have had an impact on foreign policy decisions. Aftera difficult transition, Nepal's newly elected government has just one option to operate as a balancing actbetween local, regional, and global interests. There are several reasons why Nepalese foreign policydecisions have been analyzed in this article. It is necessary to rely on non-primary sources ofinformation in order to meet the goals.